Título de la tesis: Autoestima y asertividad en estudiantes de la carrera de Psicopedagogía de la Universidad Nacional de Chimborazo - Guapi Bagua, Paul Fabian (2022)
The aim of the present study was to determine the correlation between the level of self-esteem and the level of assertiveness’ of students of sixth, seventh and eighth semester of the Psychopedagogy Career of the Faculty of Sciences of Human Education and Technologies of the National University of Chimborazo, our study variables include: self-esteem, which is affection and importance for itself, and, on the other hand, assertiveness, defined as the expressive dexterity of interpersonal communication. To achieve the objective of the study, methodologically it is a research project with a quantitative approach, non-experimental design, correlational type; by basic objective and by field location, cross-sectional; the population is made up students of the Psychopedagogy career, consolidated by a number of 81 students made up 61 women an 20 men belonging to the sixth, seventh and eighth semester, the use of standardized psychometric techniques was carried out. The Rosenberg self-esteem test was used, which gives the results; “Low self-esteem (10.98), average self-esteem (59.76). High self-esteem (29.27)”, in the same way for the variable Assertiveness, the inventory of Rathus assertiveness was used showing the following results; “Very Assertive” (4.88), Assertive “(20.73)”, Assertive Confrontational “(62.20)”, Inasertive “(9.76)”, Very Inasertive “(2.44)”. Being a correlative research project, the Pearson correlation coefficient was used, in order to determine the correlation between these two variables quantitatively, according to the SPSS program when doing the Pearson correlation between the assertiveness dimension and self-esteem was found the value: 0.186, which indicates a positive correlation, directly proportional of linear character.